Social motivation, justice, and the moral emotions : an attributional approach - Weiner, Bernard, 1935- (Lawrence Erlbaum Associates, 2006)
Appealing to practicing and research psychologists and advanced students in many fields, this book, that is divided into five chapters, proposes an attribution theory of interpersonal or social motivation that distinguishes between the role of thinking and feeling in determining action.